2011
DOI: 10.2106/jbjs.i.01375
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Outpatient Telerehabilitation for Patients Following Total Knee Arthroplasty

Abstract: therapeutic Level I. See Instructions to Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
391
3
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(427 citation statements)
references
References 42 publications
13
391
3
10
Order By: Relevance
“…Attrition bias was absent only in three trials 9,86,90 in which no patients were lost at follow up and consequently ITT and per-protocol analysis were coincident.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Attrition bias was absent only in three trials 9,86,90 in which no patients were lost at follow up and consequently ITT and per-protocol analysis were coincident.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…A research team at the University of Queensland, Australia, has developed a computer-based videoconferencing system call eHAB that combines highquality videoconferencing with a battery of measurement tools that can objectively measure various aspects of functional performance across an Internet link. Studies demonstrating the validity and reliability of this system have been performed to examine physical outcome measurements [6,10], observational kinematic gait analysis [11], upper-limb range of motion in stroke patients [12], lowerlimb range of motion in an orthopedic population [13], the effectiveness of rehabilitation following total knee replacement surgery [14][15][16], and diagnostic accuracy of ankle injuries [17]. Other studies using similar videoconferencing equipment have demonstrated that telerehabilitation assessments of Functional Reach, the European Stroke Scale, and the Functioning Everyday with a Wheelchair-Capacity can be performed accurately compared with face-to-face encounters [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Both the NP and the patient expressed high levels of satisfaction with the benefits to the patient and the IP nature of the assessment. Previous studies using telerehabilitation models for physical therapy interventions have also shown high satisfaction levels [15][16][17] and positive experiences. 7 This RPR was in place for 1 year in the remote community, so the community members were familiar with its use and had seen the benefits for emergency and pediatric care.…”
Section: Resultsmentioning
confidence: 89%
“…Intervention studies using videoconferencing (VC) have focused mainly on knee and upper-extremity issues, [7][8][9][10][11] and none have reported using an inter-professional (IP) approach. Although VC may be able to address some unique health care needs when delivering physical therapy services in remote communities, secure telehealth or VC units are not available in every community.…”
mentioning
confidence: 99%